PENERAPAN PENDEKATAN KOOPERATIF TIPE TGT PADA PEMBELAJARAN SAINS DALAM MENINGKATKAN HASIL BELAJAR ANAK DI KOTA MAKASSAR - Ramli, Syamsul Alam (Pedagogik Journal of Islamic Elementary School, 2018)
This study aims to implement a cooperative approach with the type of Team Games Tournament (TGT) model in SCIENCE learning in improving the learning outcomes of fifth grade students of Inpres Tidung Elementary School in Rappocini District, Makassar City. This research was carried out at SD Inpres Tidung, Rappocini Sub-District, Makassar City on September 5, 2011 until October 5, 2011. This study used a type of CAR (PTK) with the aim of knowing how to apply the Team Games Tournament (TGT) Cooperative Approach to SCIENCE learning in improving learning outcomes of fifth grade students of SD Inpres Tidung, Rappocini Subdistrict, Makassar City. The research target is children in class V in the academic year 2011/2012 odd semester as many as 34 children, totaling 11 boys and girls totaling 23 people. Data collection techniques through observation, documentation, and tests are analyzed through quantitative and qualitative techniques. The results show that there is an increase in children's learning outcomes in SCIENCE learning after getting learning through the Team Games Tournament (TGT) type. Learning activities in learning have increased in terms of cohesiveness in groups, asking questions during learning, children can solve problems encountered during learning, children can answer teacher's oral questions, children submit responses when learning takes place and are shown learning outcomes with test scores child.